Happy 65th Birthday Professor Mehmed Nurkanovi´c ! - Kulenović, Mustafa (Sarajevo Journal of Mathematics, 2026)
It is a great pleasure to congratulate Professor Mehmed Nurkanović, Managing Editor of Sarajevo Journal of Mathematics, on the occasion of his 65th birthday. We dedicate this issue to him in recognition of his significant scientific contributions to mathematics - particularly in the fields of difference equations and discrete dynamical systems - as well as for his devoted service to our journal.